Legal Review of Criminal Punishment of Perpetrators of the Criminal Acts of Theft with Violence Based on Social Justice (Decision Study Number: 470/Pid.B/2024/PN.Mtr) - Mahendra, Edwin Isa (KnE Social Sciences, 2025)
This study examines the punishment of perpetrators of violent theft based on social justice, with the focus on Decision Number: 470/Pid.B/2024/PN.Mtr. The main issues raised are how the punishment process is applied, what are the weaknesses and solutions, and how judges consider making decisions. Indonesia as a country of law upholds the principles of justice and the supremacy of law, but crime, including violent theft, is still a serious challenge due to social pathologies such as economic inequality and lack of legal awareness. This study uses a normative juridical method with a descriptive analysis approach, collecting data from primary, secondary, and tertiary legal materials through literature studies and document studies. Data are analyzed qualitatively with deductive logic. The results of the study show that the judge’s decision tends to be formalistic and retributive, paying less attention to aspects of victim restitution and the socio-economic background of the perpetrator. The obstacles include the lack of normative guidelines, social pressure, and the lack of alternative sanctions oriented towards restorative justice. The solution includes the implementation of comprehensive restitution, checking the social background of the perpetrator, and systematically integrating a restorative approach to realize substantive justice that is more humane and in line with social justice.